Effects of local and systemic Atorvastatin on inflammation and alveolar bone loss in experimental periodontitis in rats - Masoumi, Sara; Kouzeforush Abadi, Kamran; Setoudehmaram, Shahin; Tanideh, Nader; Movahedd, Bahram (Journal of Dental School, 2019)
Objectives The first cause of tooth loss in developed countries is periodontitis and mostly occurs in people over 40 years old.Atorvastatin is a statin drug class, which has a revolutionary impact on the treatment of high cholesterol and also stimulates bone morphogenic protein which has osteogenic potential. The aim of this study was to evaluate the effect of local and systemic Atorvastatin in the treatment of periodontitis. Materials and Methods Forty eight Sprague Dawley rats were randomly divided into six groups of eight in each; experimental periodontitis was induced by ligature in five of them in each group daily (1) systemic Atorvastatin 12.5 mg/kg (2) systemic solvent (3) local Atorvastatin 0.25 mg/kg (4) local solvent (5) no drug was administered and group (6) left non-ligated, and rats were sacrificed on 11th day. Histopathological analysis on periodontal tissue; malondialdehyde (MDA) and superoxide dismutase (SOD) tests on serum were performed to investigate bone loss and inflammation. The statistical tests for MDA and SOD samples were one-way ANOVA with Duncan post-hoc whereas in histopathological samples nonparametric Kruskal–Wallis and Mann–Whitney tests were used. Results Although local injection and oral administration of Atorvastatin significantly decreased alveolar bone loss and serum MDA levels, no significant difference in their effectiveness was observed. Serum SOD levels were not significantly changed in all administered groups. P-value < 0.05. Conclusion In this study, both local injection and oral forms of Atorvastatin decreased inflammation and bone loss in periodontitis. However, no significant difference in their effectiveness was detected. However, local injection is superior to oral form due to effective lower dose.